1988
DOI: 10.3181/00379727-188-42704
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Skeletal Muscle Satellite Cells after Castration and Administration of Testosterone Propionate

Abstract: Thirty-six neonatal pigs were randomly assigned to the following treatment groups: sham implanted gonadally intact males (B), sham-implanted castrated males (C), or castrated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…Satellite cells are direct targets of androgen action upregulating AR concentration and decreasing differentiation of porcine satellite cells in culture (20,35). Testosterone also enhances satellite cell activity and myonuclei incorporation into growing muscle fibers of the triceps brachii from postnatal pigs (43). The rat levator ani muscle also has increased satellite cell activation and myonuclei accumulation with testosterone treatment (35).…”
Section: Discussionmentioning
confidence: 99%
“…Satellite cells are direct targets of androgen action upregulating AR concentration and decreasing differentiation of porcine satellite cells in culture (20,35). Testosterone also enhances satellite cell activity and myonuclei incorporation into growing muscle fibers of the triceps brachii from postnatal pigs (43). The rat levator ani muscle also has increased satellite cell activation and myonuclei accumulation with testosterone treatment (35).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have suggested that androgens act on satellite cells or myoblasts to increase the number of myonuclei (Mulvaney et al 1988, Joubert et al 1994, Joubert & Tobin 1995 or act on myofibers to increase protein content (Sheffield-Moore et al 1999, Ferrando et al 2002, Chen et al 2008, Ophoff et al 2009b. However, despite the fact that the AR is deleted by ≥93% in hind-limb muscles of both mAR ΔZF2 lines in our study, muscle mass is virtually normal with only relative muscle mass decreased in α-actin mAR ΔZF2 TA and soleus, but all other hind-limb muscles not different to AR lox controls.…”
Section: Discussionmentioning
confidence: 99%
“…In search of this mitogen, it was found that the proliferation and differentiation of satellite cell-derived myoblasts cultured in vitro respond to various growth factors in a dose-dependent manner (10,11). Numerous studies further revealed that the proliferation and differentiation of satellite cells during muscle regeneration is profoundly influenced by innervation, the vasculature, hormones, nutrition, and the extent of tissue injury (121,224,250,332,360,410). Interestingly, satellite cells in contact with the plasma membrane of intact myofibers were found to have reduced sensitivity to mitogen stimulation (50).…”
Section: A a Brief History Of Satellite Cellsmentioning
confidence: 99%